2000
DOI: 10.1016/s1074-7613(00)80195-8
|View full text |Cite
|
Sign up to set email alerts
|

B7/CD28 Costimulation Is Essential for the Homeostasis of the CD4+CD25+ Immunoregulatory T Cells that Control Autoimmune Diabetes

Abstract: CD28/B7 costimulation has been implicated in the induction and progression of autoimmune diseases. Experimentally induced models of autoimmunity have been shown to be prevented or reduced in intensity in mice rendered deficient for CD28 costimulation. In sharp contrast, spontaneous diabetes is exacerbated in both B7-1/B7-2-deficient and CD28-deficient NOD mice. These mice present a profound decrease of the immunoregulatory CD4+CD25+ T cells, which control diabetes in prediabetic NOD mice. These cells are absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

68
1,554
8
21

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,875 publications
(1,665 citation statements)
references
References 35 publications
68
1,554
8
21
Order By: Relevance
“…NOD mice have a defect in thymic negative selection of self-reactive thymocytes that results in loss of tolerance to autoantigens [21]. In addition, NOD mice generate low numbers of regulatory T cells [22] and the suppressive effect of these cells decreases in an age-dependent manner [23]. Our data have demonstrated that systemic treatment with gal-9 can downregulate Th1-cell numbers and T-cell proliferative responses in NOD mice.…”
Section: Gal-9 Treatment Does Not Induce An Active Tolerance In Nod Micementioning
confidence: 60%
“…NOD mice have a defect in thymic negative selection of self-reactive thymocytes that results in loss of tolerance to autoantigens [21]. In addition, NOD mice generate low numbers of regulatory T cells [22] and the suppressive effect of these cells decreases in an age-dependent manner [23]. Our data have demonstrated that systemic treatment with gal-9 can downregulate Th1-cell numbers and T-cell proliferative responses in NOD mice.…”
Section: Gal-9 Treatment Does Not Induce An Active Tolerance In Nod Micementioning
confidence: 60%
“…During the past several years, CD4ϩCD25 high immunoregulatory T cells have been identified in healthy humans, and their central role in the physiologic control of autoimmunity has been demonstrated (6,7). A large number of studies have shown that Treg cells are major players in autoimmune responses in humans (8)(9)(10) and that they may be affected by immunomodulatory therapy (11,12).…”
Section: Conclusion the Strong Positive Correlation Between Clinicalmentioning
confidence: 99%
“…Mice KO for CD28 or its ligands B7-1 and B7-2 have less T reg than wt counterpart [4]. CD28 provides a costimulatory signal necessary for the thymic development and their maintenance in the periphery by promoting self-renewal [4,5].…”
Section: Introductionmentioning
confidence: 99%